Efficacy of Osteoporosis Medications for Patients With Chronic Kidney Disease: An Updated Systematic Review and Network Meta-Analysis - Chen, Chia-Hsien; Lo, Wei-Cheng; Hu, Ping‐Jen; Chan, Hsiu-Chen; Shen, Wan-Chen; Wu, Mai-Szu; Wu, Mei-Yi (Frontiers in Pharmacology, 2022)
Background Chronic kidney disease (CKD) is associated with bone and mineral metabolism. In this study we evaluated the comparative efficacies and safety of osteoporosis medications in patients with CKD or a history of kidney transplantation, and make recommendations for the best choice of osteoporosis treatment among patients with CKD or a history of kidney transplantation. Methods We systemically searched for randomized controlled trials published in PubMed, Embase, and Cochrane databases up to June 2020. Network-meta analysis was used to compare the relative effectiveness of different treatments. A random-effects model was used when heterogeneity was expected. The safety of different treatments was also evaluated in terms of reported major adverse events. Results A total of 17 studies with data from 10,214 patients who had stage 2 to 5 CKD, were receiving dialysis, or had a history of kidney transplantation were included in the network meta-analysis. Treatment with teriparatide, denosumab, alendronate, and raloxifene were all associated with a significantly reduced risk of fractures compared to treatment with placebos (teriparatide: odds ratio [OR] = 0.19, 95% confidence interval [CI]: 0.10–0.35; denosumab: OR = 0.40, 95%CI: 0.27–0.58; alendronate: OR = 0.61, 95%CI: 0.40–0.92; raloxifene: OR = 0.52, 95%CI: 0.41–0.67). The rank probability and the surface under the cumulative ranking (SUCRA) values suggested that teriparatide ranked the highest for improvement in vertebral bone mineral density [BMD] (SUCRA=97.8%), whereas denosumab ranked the highest for improvement in femoral neck BMD (SUCRA=88.3%). Conclusion Teriparatide and denosumab seem to be the most effective treatments for preventing bone loss and reducing the risk of fracture in our network comparison. However, because of the limitations and potential biases in the reviewed studies, there is still some uncertainty about the best treatment options for osteoporosis in patients with CKD or a history of kidney transplantation.